Peranan Sistem Repong Damar Terhadap Pendapatan, Asupan Makan Dan Status Gizi Balita : Studi Kasus Di Desa Pahmungan Kecamatan Pesisir Tengah Kabupaten Pesisir Barat - Desmayanti Eka Saputri; Samsul Bakri; Reni Zuraida (Jurnal Sylva Lestari, 2015)
Regions Special Purpose or KDTI (Ministry of Forestry decree No.47/Kpts-II/1998) Repong Damar indigenous forest area of 29,000 ha which is a best practice community-based forest management in the western part of Lampung Province yet known about its capacity to ensure the sustainability of human resource development primarily critical starting at the age of five or its called toddlers. This study was doing from March to April 2014 in the village of Pahmungan District of the West Pesisir. The purpose of this research is: Knowing the linkage between population and income damar tree tenure, household food expenditure, protein intake toddlers, health status and nutritional status of toddlers. Data acquisition was done through interviews to collect data ownership damar tree population, income, food expenditure, health status and food intake (food recall) as the basis for determining the toddler nutritional status of children is calculated by the method of anthropometry (Ministry of Health, 2010). Parameter optimization using the software Minitab 16. The conclusions has proven there is a real link between the role of damar agroforest system to income, health status, and nutritional status of toddlers. Found relations or real relationship between income of damar agroforest [YI] with a population of damar tree with a model [YI]i= -0.1770 +0.023150[PHN]i. Furthermore simultaneously discovered the real relationship between food expenditure (YII) with [YII] as illustrated by the model [YII]i= 1.1546 +0438 [YI]. Further simultaneously discovered the real relationship between protein intake toddlers [YIII] with food expenditure [YII] with the model [YIII]i= 17 012 +3703 [YII]. Keywords: Repong damar, income, health status and nutritional status of toddlers